Enkätundersökning om rådgivningen kring skogsbruksplaner utförda av Norra Skogsägarna - Holmström, Jon (2015)
This rapport is based on a survey that was sent to 196 randomly selected forest owners, who during 2013 ordered a forest management plan from Norra Skogsägarna. The purpose was to examine how forest owners experienced advice given by an inspector based on their forest management plan.